Fabrication and functionalization of carbon nanotube films for high-performance flexible supercapacitors. (October 2015) - Chen, Hongyuan; Zeng, Sha; Chen, Minghai; Zhang, Yongyi; Li, Qingwen
Abstract: Carbon nanotube (CNT) films have shown many promising advantages in the development of high-performance flexible supercapacitors in terms of electrode specific area, mechanical reliability under bending and stretching, electron and ionic mobility tailored for high-rate performance etc. In this review, the recent progress in the design, preparation and functionalization of CNT film based electrodes for the fabrication of high-performance flexible supercapacitors are introduced in details, including the synthesis of conductive CNT films for the electrodes of supercapacitors, and the functionalizations of CNT film with other high-capacitance materials by both mixing and in situ growth strategies for high-performance composite electrodes. Furthermore, we also discussed the assembly strategies, prototypes and electrochemical performance of flexible supercapacitors based on CNT film composite electrodes. At last, the challenges and trends of the CNT film based flexible supercapacitors are prospected as well.